Effect of Brisk Walking on Health-Related Physical Fitness Balance and Life Satisfaction Among the Elderly: A Systematic Review - Bai, Xiaorong; Soh, Kim Geok; Omar Dev, Roxana Dev; Talib, Othman; Xiao, Wensheng; Cai, Haogang (Frontiers in Public Health, 2022)
Background: Although the elderly frequently engages in brisk walking as a form of exercise, little has been reported in the literature about the effect of brisk walking on health-related physical fitness, balance, and overall life satisfaction. Objectives: The purpose of this systematic review is to determine the effect of brisk walking on the elderly’s health-related physical fitness, balance, and life satisfaction. Design: We conducted a comprehensive search from the PubMed, Web of Science, Scopus, and SPORTDiscus databases from January to September 2021. We selected studies through PICOS and conducted a systematic literature review according to the PRISMA guidelines. Results: Thirteen studies met all criteria; eleven were classed as low risk of bias, while two were classified as high risk of bias. Generally, brisk walking has been shown to improve cardiorespiratory fitness, muscular strength, and body composition. Limited evidence was presented on flexibility, muscular endurance and development and life satisfaction, and there was conflicting evidence on balance. Moreover, evidence of restriction proves that high-intensity (80%-85%) brisk walking is more effective than moderate-intensity (60%-75%) brisk walking on the aerobic capacity of the elderly. Furthermore, there was less research conducted on males. Conclusion: Brisk walking has been shown to improve cardiorespiratory fitness, muscular strength, and body composition. Other outcomes (balance, flexibility, muscular endurance, and life satisfaction) and the impact of the intensity of brisk walking on the elderly should be confirmed. Therefore, there remains insufficient research on brisk walking, while single brisk walking cannot meet requirements of elderly in terms of their health-related physical fitness, balance, and life satisfaction. Future research should aim to examine the effectiveness of combining several types of exercises to promote general health in the elderly, as the World Health Organization recommends.